Behaviour of reindeer as an indicator of an adaptation to feeding - Nilsson, Anna; Norberg, Harri; Redbo, Ingrid; Olsson, Kerstin; Åhman, Birgitta (Rangifer, 2004)
Abstract: We assessed behaviour of reindeer affected by nutritional deprivation and how they adapted to various feeding strategies. The activity pattern of 61 penned eight month old female reindeer calves was observed during 20 of a total of 42 experimental days in winter 1997. The dominant activities were lying, ruminating, intake of feed and water, and standing. Few recordings of agonistic behaviour or snow intake occured. Restricted feed intake, half the ad lib. ration of a lichen-based diet, affected the eating behaviour of the reindeer, and more animals were standing and fewer lying compared to reindeer fed ad lib. Lack of energy in the diet correlated with animals lying curled up (lying with the muzzle close to the hind legs). This behaviour could be a useful complement to other measurements and registrations when studying adaptations to various feeding regimens.Abstract in Swedish/Sammanfattning:Syftet med studien var att undersöka om, och i så fall hur renars beteende påverkades av otillräckligt näringsintag och vid anpassning till olika utfodringsstrategier. Aktivitetsmönstret hos 61 inhägnade åtta månader gamla honrenkalvar studerades under 20 av totalt 42 försöksdagar. De vanligaste beteendekategorierna genom hela försöket var ligga, idissla, intag av foder och vatten samt stå passivt. Endast ett fåtal observationer av aggressivt beteende och snöätande registrerades. En begränsad giva dvs. halva mängden av fodergivan vid fri tillgång av en lavbaserad diet påverkade djuren ätbeteende. Dessutom observerades fler djur stå passivt medan färre låg jämfört med kontrollgruppen. Under första fasen av utfodring efter restriktionsperioden låg fler djur låg ihoprullade (med mulen tätt intill bakbenet) jämfört med kontrollgruppen, vilket tolkades som ett tecken på energibrist. Beteendestudierna visade sig vara ett värdefullt komplement till övriga mätningar och provtagningar vid studier av renars anpassning till olika utfodringsregimer.
Keywords: activity; diet; energy; Rangifer tarandus.